Spor Bilimleri Fakültesi Öğrencilerinin Isınma Bilgi Düzeylerinin İncelenmesi - Çelikel, Baha Engin; Tan, Suriye; Tokgöz, Gürkan (Hasan ŞAHAN, 2025)
Bu çalışmanın amacı, spor bilimleri fakültesi öğrencilerinin ısınma bilgi düzeylerinin incelenmesidir. Araştırmanın evrenini ise Fırat Üniversitesi Spor Bilimleri Fakültesi’nde 2024-2025 yıllarında eğitim gören öğrenciler oluşturmuştur. Araştırmanın örneklemini ise bu öğrenciler içerisinden aktif olarak spor yapan 260 öğrenci oluşturmuştur. Araştırmada SPSS paket programı kullanılmış olup, tanımlayıcı istatistiklerden frekans, T testi, ANOVA testleri uygulanmış anlamlılık düzeyi (p

The aim of this study is to examine the warm-up knowledge levels of students in the Faculty of Sport Sciences. The population of the study consists of students studying at the Faculty of Sport Sciences at Firat University during the 2024-2025 academic years. The sample of the study includes 260 active athletes among these students. SPSS software was used for data analysis, and descriptive statistics, frequency distributions, t-tests, and ANOVA tests were applied, with a significance level set at p
Investigation of Warm-up Knowledge Levels of Sports Sciences Faculty Students
Keywords: Sports Science and Exercise (Other); Egzersiz ve Spor Bilimleri (Diğer)